The Geospatial data quality and metadata: Handbook - Murti, S.; Widiastuti, F. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
This handbook is intended to provide guidance on geospatial data quality and metadata management. While it can provide the reader with answers to basic questions on the latter, it does not have all the answers. The reader should also find the information and guidance helpful when dealing with important questions on geospatial data quality and metadata.